2021
DOI: 10.1371/journal.pone.0258671
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characteristics of patients seeking COVID-19 testing in a private centre in Malaysia: Is there a role for private healthcare in battling the outbreak?

Abstract: Objective This cross-sectional observational study summarized the baseline characteristics of subjects who underwent COVID-19 molecular testing in a private medical centre located in the state of Selangor in Malaysia between 1 Oct 2020 and 31 Jan 2021. We compared the baseline characteristics between subjects who were tested positive and negative of SARS-CoV-2 infection, and identified risk factors which may be predictive of SARS-CoV-2 positivity. Methods and findings A total of 36603 subjects who were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…(6.2% to 24.1%) (11,18). A study carried out in Malaysia showed that presentation with high fever increased almost 4-fold of having PCR (+) test results (21). In our study, the incidence of fever in patients diagnosed with COVID-19 was significantly higher than in COVID (-) cases (35.3% vs. 20.4%).…”
Section: Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…(6.2% to 24.1%) (11,18). A study carried out in Malaysia showed that presentation with high fever increased almost 4-fold of having PCR (+) test results (21). In our study, the incidence of fever in patients diagnosed with COVID-19 was significantly higher than in COVID (-) cases (35.3% vs. 20.4%).…”
Section: Resultscontrasting
confidence: 41%
“…In a retrospective New York study, the most common symptoms were described as fever, coughing, shortness of breath, muscle pain, and, nausea respectively (20). In a study carried out in Malaysia, though most of the confirmed cases were asymptomatic, those who presented with loss of smell/taste, fever, running nose were significantly associated with positivity due to the multivariate logistic regression analysis (21). Sahin et al revealed odd's rates of significant complaints about PCR positivity were 2.607 for fever, 2.724 for anorexia, 2.051 for cough, 2.594 for loss of smell, and 2.243 for loss of strength (6).…”
Section: Resultsmentioning
confidence: 98%
“…We find that the co-occurrence of the onset of these outbreaks is identifiable using wastewater monitoring, and moreover, HMPV was also circulating. Whereas clinical testing data are affected by individuals’ test seeking behaviors and test availability, as well as institutional reporting delays which can be weeks in duration, , wastewater data are available within 24 h of sample collection and provide information about the entire community contributing to the wastewater system. We posit that wastewater can be used to help identify the onset and offset of respiratory virus transmission events as well as the peak of such events.…”
Section: Introductionmentioning
confidence: 99%